The Relationship Between Verbal Communication And Nonverbal Communication With Patient Satisfaction Of Registration Officers At Type B Hospital, Jepara Regency - Rachel Fatwa Ramadhani; Rusnoto Rusnoto; Ahmad Farid (CV. AFDIFAL MAJU BERKAH, 2026)
Patient satisfaction is a key indicator of hospital service quality, influenced by verbal and nonverbal communication from registration staff, who act as the gateway to service. This study aims to analyze the relationship between verbal and nonverbal communication and patient satisfaction in a Type B hospital Jepara Regency. Using a cross-sectional quantitative approach, a population of 148 outpatients (aged 18-60 years) was incidentally sampled into 108 respondents using the Slovin formula. The Chi-square results showed good verbal communication (59.3%) and a value of correlation coefficient r = 0,431, good nonverbal communication (57.4%) and a value of correlation coefficient of r = 0.403, and satisfied satisfaction (53.7%), with a significant relationship (p=0.001 for both). The conclusion states that effective communication improves patient satisfaction; ongoing communication training is recommended.